2016
DOI: 10.1016/j.jallcom.2015.09.253
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural connectivity in sintered ex-situ MgB2 bulk superconductors

Abstract: We have performed combined high-resolution microstructural and grain orientation analyses to understand the key microstructural factors associated with high intergranular transport current in polycrystalline bulk forms of MgB2. The ex-situ method can produce MgB2 with relatively high packing factors; nevertheless, the connectivity of MgB2 fabricated by the ex-situ method (ex-situ MgB2) was less than that of in-situ MgB2. The poor connections between MgB2 grain aggregates cause the low connectivity of ex-situ M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Simultaneously, a uni-axial pressure is applied. The main difference between SPS and conventional or hot-pressing methods is that SPS allows for the preparation of highly dense samples with grain growth control and a decreased processing time [ 13 , 14 , 15 , 16 ]. Concerning MgB 2 , the samples processed by SPS additionally show excellent mechanical properties [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, a uni-axial pressure is applied. The main difference between SPS and conventional or hot-pressing methods is that SPS allows for the preparation of highly dense samples with grain growth control and a decreased processing time [ 13 , 14 , 15 , 16 ]. Concerning MgB 2 , the samples processed by SPS additionally show excellent mechanical properties [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The electron backscatter diffraction technique (EBSD) has recently proven to yield important results concerning the crystallographic orientation of the grains (Mikheenko, 2012;Wong et al, 2015;Koblischka-Veneva et al, 2016;Shimada et al, 2016). Due to the small size of the MgB 2 grains, it turned out that the newly developed transmission EBSD (t-EBSD) technique is better suited for the investigation of such samples, enabling a higher spatial resolution and being less influenced by charging effects etc.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the sample density increased for excess Mg content up to 5 mol%. However, T c decreased slightly (* 1.5 K) with the addition of excess Mg [17].…”
Section: Introductionmentioning
confidence: 96%
“…It is known that the coupling of grains across grain boundaries (grain coupling) for ex situ samples is weaker than that of in situ ones, though the former has a higher packing factor of * 75% [3]. Unlike the stronger grain coupling in in situ MgB 2 , the pre-reacted ex situ MgB 2 grain aggregates are poorly connected, leading to the reduced effective cross-sectional area for current transport, thus lower J c [14,17]. If the grain coupling of the ex situ samples is improved, their J c should outperform that of the in situ MgB 2 .…”
Section: Introductionmentioning
confidence: 99%